Potential Use Of Ozonation With Limestone Adsorption Process In Groundwater Treatment - Akbar, Nor Azliza (2019)
One of the major problems related to groundwater is the presence of iron (Fe) and manganese (Mn) from natural processes and anthropogenic activities which causes groundwater to turn red-brown in colour. Besides, high natural organic matter (NOM) content influences the water organoleptic quality and potential to produce by-product after chlorination known as disinfectant by product (DBP). Therefore, this study was aimed at investigating the potential of different adsorbents (limestone and anthracite) in treating Fe and Mn, colour and NOM from groundwater at Universiti Sains Malaysia (USM) and Pintu Geng horizontal well by multiple stage ozonation process including single ozonation, ozonation-limestone and integrated ozonation-anthracite processes. Water quality analysis of USM well was not recommended to be used as drinking water due to high organic content, Fe (1.23mg/L) and Mn (0.56mg/L). The monitoring data for Fe concentration at Pintu Geng horizontal well between December 2013 and August 2014 recorded the level ranging from 0.16-2.05mg/L, which exceeded the permissible limit of drinking water. Limestone is rich of hydrophilic groups (O-H and C=O) and it has the capability to adsorb Fe and Mn. In comparison, the functional groups present on the anthracite surface are mostly of hydrophobic groups (C-C and C-H), which are beneficial for adsorbing organic compound. Limestone was found capable of removing 96.7%, 87.6%, 15.8% and 32.4% of Fe, Mn, colour and UV254, respectively. On the other hand, the removals of Fe, Mn, colour and UV254 by anthracite were 51.2%, 32.4%, 59.9% and 78.5%, respectively. Analysis of isotherm showed that the adsorptions of Fe and Mn onto limestone fitted the Langmuir model and the Pseudo-second order kinetic in kinetic study which were associated with chemisorption. The adsorptions of colour and UV254 onto anthracite fitted the Temkin isotherm model and the Pseudo-first order kinetic which were associated with physisorption. The use of ozone alone only removed 72% and 58% of Fe and Mn, respectively. The final effluent after ozonation process still exceeded the maximum allowable limit for drinking. However, ozonation was useful as a disinfectant, which had destroyed 100% total coliform through this process. The ozonation process alone was capable of removing colour to below than the permissible limit (< 15 PtCo), as well as removing 79% of UV254. The fixed-bed column using an integrated ozone-limestone adsorption exhibited 99.5% and 92% reduction in Fe and Mn respectively and complied with the drinking water standard. The integrated ozone-anthracite adsorption process had successfully removed 92.2% of Fe. However, the treatment system was found not effective to remove Mn with only 43.3% reduction. Therefore, the integrated treatment of ozonation with limestone adsorption was suggested as an alternative process to treat Fe and Mn in groundwater.